Gomery's blinders and Canadian federalism - Hubbard, Ruth, 1942- (Book collections on Project MUSE., 2007)
In 2004, Paul Martin asked Justice John Gomery to lead a public inquiry into potential misspending in the federal Sponsorship Program, a relatively small investment of taxpayers' money to try to convince Quebeckers of the benefits of Canadian federalism in the aftermath of the 1995 referendum on Quebec separation. The Gomery inquiry chose to focus exclusively on the sordid details of the money laundering and paid no attention to the deeper causes and sources of the problem: the dysfunctions of an existing centralized governing apparatus that is tearing the fabric of the country apart and the co.